"Navigating" through a scientific career: A question of private and professional configurational supports. (May 2017) - Fusulier, Bernard; Barbier, Pascal; Dubois-Shaik, Farah
Men and women remain in unequal positions in coping with their scientific and academic careers. Several of the mechanisms dissuading or preventing women from pursuing scientific careers have already been described in the literature: women getting stuck with paltry, undervalued tasks, thus manufacturing a "sticky floor"; structuring the scientific field around a masculine habitus; and the "Matilda" effect for women. An additional cause of these inequalities is observed in the relationship between the private and professional aspects of the individuals' lives. The university transmits a "gendered order" in its organizational structures, principles, customs and habits, in short in the practice of scientific work. That is due in particular to the ancient structuring of the university around a male figure: the "university professor" or "scientist" entirely invested in his work, freed from domestic necessities by an invisible carer (he or she who 'cares' for him), so he can devote himself to science. Hence the university was constructed on a "greedy" model expecting a total, voluntary and impassioned engagement in work, coupled with a model of work/family dissociation. Based on a research programme dealing with post-doctoral researchers and recently tenured researchers*, this article analyses the role of their private life and how it relates to the professional sphere in their experience of scientific work. In this respect, it provides some explanatory elements on both the greater vulnerability of women-mothers in the university game and on the configurational supports (configurations of professional life and private life) needed to offset that vulnerability.